A systematic review of global COVID-19 vaccine PPPs: drivers and barriers to governance alignment - Qi, Xuejing (Frontiers in Public Health, 2025)
BackgroundPublic-private partnerships (PPPs) have emerged as a prominent governance model for vaccine equity in the COVID-19 vaccine supply chain. Previous studies focus on evaluating PPP’s performance, lacking multi-dimensional analysis on the drivers and barriers that shape public and private actors’ willingness to participate in PPPs.MethodFollowing the PRISMA 2020 guidelines, a systematic review using the Web of Science (WoS) database was conducted to identify empirical factors influencing stakeholders’ preference for PPPs and the alignment between sectors was explored by qualitative content analysis.ResultsThree main categories of private sector drivers were identified, including regulatory facilitation, financial incentives and reputational incentives. While four sets of barriers emerged, including the political environment, economic and logistic constraints, and the contractual obligations. For the public sector, motivations centered on ethical considerations, national interest protection, and institutional advantages, while participation was also constrained by vaccine nationalism and administrative lag. The analysis demonstrates the degree of alignment and misalignment among these governance factors.ConclusionBased on the analysis of factors, this study proposes the Governance Alignment Framework (GAF) as a conceptual tool to pair the profits of different sectors and guide governments and public sectors to improve the developmental-steering capacities to better align private incentives with public value during the pandemic.